A MECHANISM FOR MONITORING THE LEVEL OF EDUCATION AMONG LEARNERS - Abdullayev , Mehriddin Junaydilloyevich; Jamilov , Shohruz Tavakkalovich (Educational Research in Universal Sciences, 2023)
This article describes the importance of the cluster module system in popularizing sports among students in the higher education system and improving the health of young people with health problems.